The Security Period as a Mechanism to Consecrate the Power of Criminal Governance in Accordance with Algerian Legislation - Benyounes, Farida (Journal of Legal Studies and Researches, 2021)
The principle is for the convicted person to be deposited with the penal institution for the rehabilitation, reform and social reintegration programs to be applied to him. If the latter is responded to, the content of the penal judgment possessing the power of the adjudicated matter may be changed and modified in line with the degree of response to the established programs, and to achieve more effectiveness in the judiciary on crime. On the other hand, there are crimes of gravity and gravity, which require strict application of them and not allow the prisoner to benefit from the systems of punishment measures for a specific period, which is the security period that is the subject of our study.